DESIGUALDADE NA BAHIA: UMA ANÁLISE ESTRUTURAL DOS CONDICIONANTES SOCIOECONÔMICOS, POLÍTICOS E CULTURAIS DA DESIGUALDADE NO ESTADO DA BAHIA NO PERÍODO 1946 - 2006 - Aragão, Gilton Alves (2011)
The study of the inequality in the state of Bahia in the period 1946 to 2006, through an interdisciplinary analysis of socioeconomics conditions, political and cultural inequality, is the theme that characterizes the present thesis. Backed in a theoretical framework consisting of authors of the Marxist trend and CEPAL, besides relevant conceptions on regional development, initially presents an overview of the capitalist world, focus on Brazilian society, emphasizes the Brazilian Northeast and highlights that the process of industrialization, was characterized by inequality, legitimized by economic planning. The study then focuses on the three types of this inequality constraints in Bahia. First, in the socio-economic area, it was treated the aspects concerning the performance of major sectors; of the government strategies and of the role of business and cooperative ventures. Second, in the analysis of political constraints, it was studied the division of groups of Bahia s organized society and the role of each in the establishment of measures designed to meet their needs. Third, in cultural terms, the study found the engagement of the majority of the population in the political process and the existence of social segregation that result in the denial of opportunities that could reduce inequality. Then, sows the discussion of the results; presents the conclusion and, finally, the bibliographic references that underlie the search for the preparation of this thesis.